Handbook of personnel management and labor relations - Yoder, Dale.; Heneman, H. G. (New York : McGraw-Hill, 1958)
This handbook has been designed to meet the need of those who carry responsibility for leading and managing people, including executives and line managers and supervisors, as well as specialists in personnel administration and labor relations. The book is further designed with special concern for the day-to-day problems faced by practitioners in the field of employer-employee-union relationships.
Section 1(1.1-1.35), Section 2(2.1-2.43), Section 3(3.1-3.31), Section 4(4.1-4.55), Section 5(5.1-5.45), Section 6(6.1-6.36), Section 7(7.1-7.39), Section 8(8.1-8.57), Section 9(9.1-9.33), Section 10(10.1-10.51), Section 11(11.1-11.37), Section 12(12.1-12.62), Section 13(13.1-13.44), Section 14(14.1-14.72), Section 15(15.1-15.35), Section 16(16.1-16.81), Section 17(17.1-17.41), Section 18(18.1-18.38), Section 19(19.1-19.33), Section 20(20.1-20.38), Section 21(21.1-21.46), Section 22(22.1-22.42), Section 23(23.1-23.73), Section 24(24.1-24.37), Section 25(25.1-25.41).
Includes bibliographical footnotes and index.
hza 12/07/2018
Loans
Keywords: Personnel management